Quantification of pressure‐induced γ‐crystals in isotactic polypropylene: The influence of shear and carbon nanotubes. Issue 1 (23rd March 2018) - Lin, Jian‐Mei; Yang, Shu‐Gui; Hu, Bo‐Chuan; Song, Ying‐Nan; Ren, Jia‐Yi; Lei, Jun; Ji, Xu; Li, Zhong‐Ming
Abstract: Using a homemade pressuring and shearing device (PSD), we systematically studied the γ‐crystals formation of iPP/CNTs composites under various pressures and shear rates. Interestingly, CNTs and shear revealed multiple‐effects on γ‐iPP formation under pressure. The combined effects of CNTs and shear on γ‐phase formation only met a simple additive principle at 0.1 or 150 MPa or a weak shear. However, when the pressure was 50 or 100 MPa at a relatively high shear rate, the coexistence of CNTs and shear showed a synergetic suppressing effect on γ‐phase formation, and this effect became very evident with increase in shear rate. In addition, pressure‐induced γ‐crystals exhibited a strong shear rate dependence, and the critical shear rate for suppression to γ‐form formation decreased with the addition of CNTs and increased by elevated pressure. These significant results could help adjust the structure of iPP in practical processing to fabricate products with desired performance. Abstract : Carbon nanotubes (CNTs) and shear revealed multiple‐effects on pressure‐induced γ‐iPP formation. The combined effects of CNTs and shear on γ‐phase formation only met a simple additive principle at 0.1 or 150 MPa or a weak shear; however, when the pressure was 50 or 100 MPa at a relatively high shear rate, the coexistence of CNTs and shear showed a synergetic suppressing effect on γ‐phase formation, and this effect became very evident with increase in shear rate.